Estudo da propagação vertical das ondas de gravidade de pequena escala observadas na Estação Antártica Comandante Ferraz nos anos de 2015 a 2017 - Giongo, Gabriel Augusto (2020)
This dissertation had the objective of identification and analysis of the vertical propagation conditions and possible sources of the gravity waves observed over the Comandante Ferraz Antarctic Station (EACF: 62.1° S; 58.4° W). It was investigated three years of airglow observations, in the hydroxyl near-infrared emission band (approximately between 84 and 88 km height). Wave parameters were obtained by a two-dimensional discrete Fourier Transform applied at the region of the images where a wave event was identified, returning the horizontal wavelength, observed period, phase speed, and propagation direction of the waves. Vertical propagation conditions and the wind filtering were verified, respectively, by analysis of the vertical wavenumber (m²) and by blocking diagrams. The vertical wavenumber and the intrinsic parameters were calculated with wind data from a meteor radar deployed at King Sejong Station (KSS), at the same island (King George) where EACF is, and by temperature data obtained by satellites. A ray-tracing model was utilized to estimate the wave propagation thru the atmosphere and the origin regions of these wave events. Among all the observed waves in the three years (522 cases), most of them presented wavelengths between 20 and 35 km, periods between 5 and 15 min, and phase speeds between 20 and 80 m/s. Among the waves in which the vertical propagations were analyzed, all waves were considered vertically propagating, and wave filtering is seen at heights near the observation layer. The blocking diagrams showed the anisotropy in the wave propagation direction. The ray-tracing returned, for 111 gravity wave cases, that mostly waves could originate at distances less than 500 km (in a straight line) from the observation site, at altitudes inside the mesosphere (33 %), some cases in the stratosphere (17 %), various cases (37 %) at troposphere (below 20 km), and for a few cases (13 events, 12 %) the model stopped at firsts iterations. The model could not relate tropospheric sources to the observed gravity waves.